From Data Modeling to Knowledge Engineering in Space System Design - Hennig, Christian (KIT Scientific Publishing, 2017)
The technologies currently employed for modeling complex systems, such as aircraft, spacecraft, or infrastructures, are sufficient for system description, but do not allow deriving knowledge about the modeled systems. This work provides the means to describe space systems in a way that allows automating activities such as deriving knowledge about critical parts of the system's design, evaluation of test success, and identification of single points of failure.